The Mediating Role of Hope in the Relationship between Social Phobia and Resilience, and Subjective Well-being among Students - Maryam Ghavidel; Heydar Ali Zarei (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Hope, as a key psychological force, can affect the relationship between psychological variables. Therefore, this study aimed to determine the mediating role of hope in the relationship between social phobia and resilience with mental well-being. Materials and Methods: This was a descriptive-correlational study. Participants included 257 students of Islamic Azad University of Marand branch who were selected using randomized cluster sampling. Data were collected using Miller's Hope Questionnaire, Connor Social Phobia Questionnaire, Conner and Davidson's Resilience Scale, and Ryff Mental Well-Being Scale. Collected data were analyzed in SPSS-24 and AMOS-22 statistical softwares using descriptive statistical methods and Pearson correlation test and path analysis. Results: In this study, 128 (48%) participants were female and 139 (52%) were male. The mean (SD) subjective well-being score was 203.3 (33.5), resiliency 90.5 (14.8), hope 171.7 (19. 4) and social phobia 38.1 (12.1). As social phobia increased, subjective well-being decreased: r=-0.16, P<0.01. However, with increasing resilience, subjective well-being increased: r=0.24, P<0.01. In addition, hope partially mediated the relationship between resilience with subjective well-being (P<0.05), and mediates the relationship between social phobia and subjective well-being completely (P<0.05). Conclusion: Hope as a mediating variable fully affected the relationship between social phobia and subjective well-being and partially affected the relationship between resilience and subjective well-being. DOI: http://doi.org/10.22037/ch.v5i4.19477